Elements Of Work Type In The Construct Of Special Education Teacher Workload In Malaysia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In discussing the workload of teachers, some important elements will certainly be refined. Among the relevant elements are the elements of time, work environment and resources. All of these elements are able to influence the workload experienced. Many studies have proven that, task management will become disorganized if the relevant elements become constraints. If it is dedicated to special education, elements such as student categories, working hours and workload are also factors in the workload. In addition to the elements already mentioned, the most impactful element is the type of assignment received. It can be explained that, the form of assignments as well as assignments received themselves will be a factor in the occurrence of the workload of special education teachers. A qualitative study with this interview method was conducted by involving 11 special education program coordinators for each district in the state of Johor as respondents. The findings show that, the majority of respondents acknowledged that the type of task is a key element of their workload.